تأثير تمارين خاصة في تطوير دقة التهديف للركلات الثابتة المباشرة من منطقة الجزاء لنادي العلوم بكرة القدم - عبدالأمير، يوسف; سبهان، ميثم حبيب; خلف، صباح قاسم (جامعة بغداد - كلية التربية البدنية وعلوم الرياضة, 2015)
The first chapter included the interlocution and the importance of the research. The importance lies in close range shots in the penalty area as well as the ability to concentrate attention in performing the skill. The problem of the study, the hypotheses and the aims are all discussed in this chapter. Chapter two included theoretical studies including the concept of attention, shooting skill in soccer, close range shots in penalty area, etc. Chapter three tackled the field procedures including using the experimental method, the selection of the subjects, tests used, etc. Chapter four displayed, discussed and analyzed the results that the researchers came up with in relation to identifying the effect of special exercises and concentrating attention to develop the accuracy of shooting in the penalty area. Chapter five included the conclusions and recommendations. The most important conclusion was that there is a development in the level of performance that came as a result of developing the results of shooting accuracy.
تضمن الباب الأول التعريف بالبحث وأهميته، وتم التطرق إلى أهمية الركلات الثابتة القريبة من منطقة الجزاء في دقة تأدية المهارة، وتم التطرق الى مشكلة البحث والسبب في خوض هكذا بحوث، والتعرف على أهداف وفروض البحث وكذلك مجالاته. أما الباب الثاني احتوى على الدراسات النظرية، فقد تم التطرق الى التعرف على مفهوم مهارة التهديف والركلات الثابتة القريبة من منطقة الجزاء. اما الباب الثالث فقد تم التطرق الى الاجراءات الميدانية، حيث تعرفنا على المنهج البحث المستخدم وهو البحث التجريبي وعينة البحث والاختبارات المستخدمة في البحث. وكان الباب الرابع احتوى على عرض وتحليل ومناقشة النتائج التي توصل اليها الباحثين، ومعرفة تأثير التمارين الخاصة في تطوير دقة التهديف للركلات الثابتة موضوع البحث. اما الباب الخامس فاحتوى على الاستنتاجات والتوصيات التي توصل اليها الباحثين، ومن اهم الاستنتاجات ان هناك تطور في مستوى الأداء المهارى لدى عينة البحث من خلال تطوير نتائج دقة التهديف من الثبات.
Keywords: التدريب الرياضي -- التمرينات الخاصة -- مهارات التهديف -- كرة القدم